In vivo enhancement of peptide display by MHC class II molecules with small molecule catalysts of peptide exchange. - Call, M; Xing, X; Cuny, G; Seth, N; Altmann, D; Fugger, L; Krogsgaard, M; Stein, R; Wucherpfennig, K (2009)
Rapid binding of peptides to MHC class II molecules is normally limited to a deep endosomal compartment where the coordinate action of low pH and HLA-DM displaces the invariant chain remnant CLIP or other peptides from the binding site. Exogenously added peptides are subject to proteolytic degradation for extended periods of time before they reach the relevant endosomal compartment, which limits the efficacy of peptide-based vaccines and therapeutics. In this study, we describe a family of small molecules that substantially accelerate the rate of peptide binding to HLA-DR molecules in the absence of HLA-DM. A structure-activity relationship study resulted in analogs with significantly higher potency and also defined key structural features required for activity. These compounds are active over a broad pH range and thus enable efficient peptide loading at the cell surface. The small molecules not only enhance peptide presentation by APC in vitro, but are also active in vivo where they substantially increase the fraction of APC on which displayed peptide is detectable. We propose that the small molecule quickly reaches draining lymph nodes along with the coadministered peptide and induces rapid loading of peptide before it is destroyed by proteases. Such compounds may be useful for enhancing the efficacy of peptide-based vaccines and other therapeutics that require binding to MHC class II molecules.